2009
DOI: 10.1073/pnas.0905851106
|View full text |Cite
|
Sign up to set email alerts
|

Epimorphic regeneration approach to tissue replacement in adult mammals

Abstract: Urodeles and fetal mammals are capable of impressive epimorphic regeneration in a variety of tissues, whereas the typical default response to injury in adult mammals consists of inflammation and scar tissue formation. One component of epimorphic regeneration is the recruitment of resident progenitor and stem cells to a site of injury. Bioactive molecules resulting from degradation of extracellular matrix (ECM) have been shown to recruit a variety of progenitor and stem cells in vitro in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
134
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 143 publications
(136 citation statements)
references
References 57 publications
2
134
0
Order By: Relevance
“…Another potential contributing cell population is the multipotent perivascular stem cell. 22,29 Perivascular stem cells are found surrounding the endothelium of normal tissue and are likely to be present in the vasculature within the esophagus. A number of studies have reported the chemotactic and mitogenic potential of ECM for the perivascular stem cell population.…”
Section: Discussionmentioning
confidence: 99%
“…Another potential contributing cell population is the multipotent perivascular stem cell. 22,29 Perivascular stem cells are found surrounding the endothelium of normal tissue and are likely to be present in the vasculature within the esophagus. A number of studies have reported the chemotactic and mitogenic potential of ECM for the perivascular stem cell population.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, ECM materials derived via decellularization of a variety of allogeneic or xenogeneic source tissues have been shown to induce a phenotypic transition from the proinflammatory macrophage and lymphocyte phenotype toward a regulatory, "anti-inflammatory" and healing phenotype [9,31,32,33], and to promote endogenous stem/progenitor cell activation and recruitment [11,29,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…14 C-labeled ECMH was prepared as stated above with the intestines of pigs that were injected with 14 C-tagged proline, as previously described [15]. FITC-labeled ECMH was prepared with a protein labeling kit (Thermo PierceNet) per manufacturer's instructions [11].…”
Section: Ecm Hydrogel Preparation and Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 The mechanisms of action are not fully understood, but site-appropriate remodeling is hypothesized to be a consequence of immune modulation, promotion of angiogenesis, and recruitment of progenitor cells. Despite a high risk of poor healing and a permanent stoma associated with the magnitude of this anastomotic defect, 2,3,5 it appears that the salutary properties of MatriStem 7,8,9 enabled successful healing of this anastomotic defect. The defect healed rapidly and was associated with healthy vascularized tissue with no evidence of scarring or stricture that typically occurs after an anastomotic leak.…”
Section: Discussionmentioning
confidence: 99%